Testosterone supplementation and stroke in young adults: a review of the literature - Dengri, Chetna; Koriesh, Ahmed; Babi, Marc A.; Mayberry, Whitney; Goldstein, Eric D.; Pervez, Mubashir; Nouh, Amre (Frontiers in Neurology, 2024)
Testosterone supplementation has increased in recent years for both treatment of hypogonadism and recreational use. Strokes in young adults have similarly increased with a larger proportion of patients in this age group having a stroke due to early onset of cardiovascular risk factors or unrelated to conventional risks. Hormonal treatments are associated with increased stroke risk amongst women, with some studies indicating an increase in stroke risk as high as 40% when compared to non-users. However, less is known about male sex hormones and risks associated with increased stroke. Limited data evaluates the relationship between testosterone supplementation and stroke in young adults. In this review, we analyze the literature and plausible underlying pathophysiological mechanisms associated with increased risks in patients using exogenous testosterone. Furthermore, we highlight the gaps in research about safety and long-term effects on young patients.